Do Demiurgo ao Hacker: Tecnologia e Auto-Organização - Pereira Júnior, Alfredo [UNESP] (My University, 2012)
In this essay, I make an approach to two models of technological work, corresponding to the philosophies of Plato and Aristotle. In Plato, we can find a model of heteroorganization, in which material beings are conceived as imperfect copies of ideal templates, by means of the action of a Demiurge. In Aristotle, we find a model of self-organization, in which the Form and the Matter that constitute natural beings influence each other, defining their identity. Two extrinsic causes also operate, the Efficient and Final ones, revealing the compatibility of hetero and self-organization. In the Modern epoch, we observe in social institutions the dominance of the hetero-organizing model, accompanied by a contemporary tendency towards resuming the self-organizing model. This can be seen in creative actions, such as those referred by the terms ‘tinkering’, ‘bricolage’, ‘recycling’, ‘remix’, all symbolized in the figure of the Hacker, the subject who descontructs an existing product and uses its parts to carry new functions.

Neste ensaio, abordo dois modelos do trabalho tecnológico, que correspondem às filosofias de Platão e Aristóteles. Em Platão, encontramos um modelo de hetero-organização, em que os seres do mundo material são concebidos como cópias imperfeitas de modelos ideais, instanciadas pela ação de um Demiurgo. Em Aristóteles, encontramos um modelo de autoorganização, em que a forma e a matéria constituintes dos seres se influenciam reciprocamente, definindo sua identidade; as duas causas intrínsecas (forma e matéria) combinam-se com causas extrínsecas (eficiente e final), o que revela uma compatibilidade entre a auto e hetero-organização. No contexto moderno, observamos a hegemonia do modelo hetero-organizativo nas instituições sociais, ao lado de uma tendência contemporânea de resgate do modelo auto-organizativo em atividades inovadoras, o que transparece nas concepções de 'tinkering', 'bricolage', reciclagem, 'remix', simbolizadas na figura do 'Hacker' ou "gambiarrista", aquele que reaproveita um produto existente com vistas a novas utilizações, diferentes da original.
From the demiurge to the hacker: technology and selforganization
Keywords: Self-Organization; Hetero-Organization; Form; Matter; Technology; Auto-Organização; Hetero Organização; Forma; Matéria; Tecnologia